PENGARUH WORK LIFE BALANCE DAN BEBAN KERJA TERHADAP STRES KERJA PADA KARYAWAN PT BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG PONTIANAK - Dewi Persik; Maulana Filani Rizal; Angga Hendharsa (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2025)
In the modern workplace, high work pressure and demands are the main factors affecting employee well-being. Excessive workloads and unbalanced working conditions can cause prolonged work stress. One of the factors contributing to work stress is Work-life balance, which is a condition of physical, emotional, and mental fatigue caused by excessive workloads without adequate balance between work and personal life. This study aims to examine the effect of work-life balance and workload on work stress among employees of PT Bank Negara Indonesia (Persero) Tbk, Pontianak Branch Office. The method used in this study is quantitative with a survey approach, using primary data obtained through questionnaires distributed to 84 respondents who are permanent employees of Bank BNI, Pontianak City Branch. The analytical tool used to process the data is SPSS, which is an analytical method for testing the relationship between variables. The results of the study indicate that Work-Life Balance does not have a positive and significant effect on Work Stress and Workload has a significant effect on work stress. These findings indicate the importance of work-life balance and Workload in influencing work stress in employees.